The impact of digital transformation on the adoption of modern management accounting methods in commercial bank governance - Alduneibat, Khalid Ali (Asian Economic and Financial Review, 2025)
With the rapid advancement of digital technologies, financial institutions are increasingly required to upgrade their management accounting practices to stay competitive and meet evolving regulatory demands. This study examines the influence of digital transformation (DT) on modern management accounting techniques within Jordanian commercial banks. Adopting a descriptive-analytical methodology, the research focuses on how the main dimensions of DT technology, processes, and people affect accounting practices in the banking sector. Primary data were gathered through a questionnaire distributed to 228 accounting professionals across 12 major Jordanian commercial banks. The collected data were analyzed using SPSS to assess the relationship between DT and innovations in management accounting. Findings reveal that DT significantly affects all areas of management accounting, particularly by enhancing data accessibility, promoting real-time reporting, and supporting timely, informed decision-making. These improvements are driven by digital tools, automation, and process integration, all of which are essential for achieving strategic advantage and operational efficiency. This research contributes to the growing body of literature by providing empirical evidence from the Middle Eastern financial sector, specifically Jordan. It emphasizes the importance of investing in digital infrastructure and human capital to strengthen accuracy, responsiveness, and profitability in banking operations under increasing digital and competitive pressures.